European Social Services in Transition - an Introduction - Walter Lorenz (Social Work & Society, 2006)
In view of the fundamental changes in social policy witnessed in all types of welfare states Social Work and Society launches a series of papers that examines the effects of those changes on key "welfare regimes". The series will test the hypothesis that globalization and the corresponding advance of neo-liberal social policy trends have brought about a convergence of the distinct welfare traditions which Esping-Anderson characterized as "welfare regimes". Convergence would mean that the ability of national governments to steer particular policy courses according to political values has become severely restricted and that supra-national factors leave national governments little choice but to conform to economic "necessities". This is indeed often being put forward as a means of justifying the dismantling of established social service structures and the introduction of market principles in their delivery.